Rising Sea Level: Legal Consequences on the Shifting of Coastal State Baseline - Narnina, Ratu Gita; Afriansyah, Arie (Padjadjaran Journal of International Law, 2019)
AbstractBaseline is a line drawn from the coastal configuration features, which is very important because the drawing of a baseline allows a coastal State to claim its own maritime zone as measured from said line. However, this concept of baseline currently faced new phenomena called the sea-level rise caused by the climate change. Climate change is caused by the accumulation of greenhouse gas emissions in the atmosphere and causing the earth's surface temperature and sea surface temperatures to increase causing the melting of ice and glaciers. Based on survey data Fifth Assessment Report conducted by the Intergovernmental Panel on Climate Change (IPCC), it is said that in 2100 the rise of sea water will reach 0.52m to 0.98m. In this regard, the rise of seawater brings a legal implication of the possibility in a shift of the baseline due to the inundation of the coastline used as a place to draw the baseline itself, resulting in the possibility of States losing juridical claims in its maritime zone. Coastal States must now begin to have awareness regarding the impacts caused by rising sea level in order to anticipate and reduce the impact of rising sea level.Keywords: Baseline, Climate Change, Maritime Zone, Rising-Sea Level. AbstrakGaris pangkal merupakan garis yang ditarik dari fitur-fitur konfigurasi pantai yang sangat penting karena penarikan garis pangkal memungkinkan suatu negara untuk mengklaim zona maritim miliknya, diukur dari garis tersebut. Akan tetapi, garis pangkal ini kini menghadapi kendala yaitu fenomena kenaikan air laut yang disebabkan oleh perubahan iklim. Perubahan iklim disebabkan karena menumpuknya gas emisi rumah kaca dan menyebabkan suhu permukaan bumi dan suhu permukaan air laut meningkat sehingga menyebabkan mencairnya es dan gletser di bumi. Dari kejadian tersebut lahirlah fenomena yang dinamakan kenaikan air laut. Berdasarkan data dari survei yang dilakukan oleh Intergovernmental Panel on Climate Change (IPCC) dalam Fifth Assessment Report, dikatakan bahwa pada tahun 2100 kenaikan air laut akan mencapai 0,52m hingga 0,98m. Dalam hal ini, kenaikan air laut akan membawa implikasi hukum terkait kemungkinan adanya pergeseran pada garis pangkal dikarenakan tergenangnya wilayah garis pantai yang digunakan sebagai tempat untuk menarik garis pangkal, sehingga besar kemungkinan terjadinya hilangnya klaim yuridis pada zona maritim tertentu. Negara-negara pantai sekarang sudah harus menyadari dampak yang disebabkan oleh kenaikan air laut ini sehingga kemudian dapat mengantisipasi dampak dari kenaikan air laut.Kata Kunci: Garis Pangkal, Perubahan Iklim, Zona Maritim. Kenaikan Air Laut